2022
DOI: 10.1155/2022/6204795
|View full text |Cite
|
Sign up to set email alerts
|

Research on Optimization of Structural Parameters of Equipment Cabin Bottom Cover

Abstract: Since the railway vehicle structure has lots of parameters and several complex constraints, this study establishes a method for structural parameter optimization based on sensitivity analysis and surrogate models. Fatigue crack problem of the equipment cabin bottom cover of the EMU is taken as an example to optimize its structural parameters. First, establish the finite element (FE) model of the bottom cover and compare it with the bench test results to verify the accuracy of the load and restraint conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The EMU vehicle body is designed to withstand an aerodynamic load of 4 kPa when running at 250 km/h. 25 Moreover, since the measured aerodynamic load is smaller than the design standard, [7][8][9][10] it can be inferred that the stress range generated by the aerodynamic load is within the elastic limit of cabin material, resulting in linear dynamic stress. Consequently, the dynamic stress of the equipment cabin can be decomposed into distinct sub-zones, enabling the application of the superposition principle to more precisely evaluate the stress characteristics of each individual sub-zone.…”
Section: Sub-zone Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EMU vehicle body is designed to withstand an aerodynamic load of 4 kPa when running at 250 km/h. 25 Moreover, since the measured aerodynamic load is smaller than the design standard, [7][8][9][10] it can be inferred that the stress range generated by the aerodynamic load is within the elastic limit of cabin material, resulting in linear dynamic stress. Consequently, the dynamic stress of the equipment cabin can be decomposed into distinct sub-zones, enabling the application of the superposition principle to more precisely evaluate the stress characteristics of each individual sub-zone.…”
Section: Sub-zone Descriptionmentioning
confidence: 99%
“…Previous studies demonstrated that upon entering a tunnel, the surrounding air density was altered, inducing pressure waves that propagated along the tunnel. 8 The abrupt changes in pressure differentials within the equipment compartment stemmed from the transmission of compression and rarefaction waves. 4,32 These waves triggered a cycle of fluctuating peaks and troughs until the train emerged from the tunnel.…”
Section: Aerodynamic Load Characteristics Of Equipment Cabinmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the inversion can achieve good results or not mainly depends on the performance of the surrogate model. Over the past few decades, several surrogate models have been most widely used, including support vector regression (SVR) [31], kriging (KRG) [32], and radial basis function (RBF) [33]. By comparing diferent models, the results show that SVR has some advantages in terms of sparsity, accuracy, and fexibility, especially in dealing with small samples and nonlinear problems.…”
Section: Inversion Model Constructionmentioning
confidence: 99%